Study on Epistatic Effects and QTL × Environment Interaction Effects of QTLs for Panicle Length in Rice （Oryza sativa L.） - CAO Gang-qiang; ZHU Jun; HE Ci-xin; GAO Yong-ming; WU Ping (浙江大学学报. 农业与生命科学版)
QTLs with epistatic effects and environmental interaction effects for panicle length of rice were studied by mixed-model based QTL mapping with a doubled haploid population from IR64/Azucena in four environments. The results demonstrated the importance of epistasis as a genetic basis of the quantitative traits and also revealed several important features of this phenomenon. In the results, all QTLs except two were involved in epistasis, and 64.7 per cent of the QTLs involved in epistasis were found with significant additive effects. This might mean that the usual estimates of the QTL additive effects could be confounded by epistatic interactions and result in biased estimation. The other 35.3 per cent QTLs did not have any significant additive effects of their own but were also involved in epistatic interactions. Such loci might play the role of modifying agents that tend to activate other loci or modify the action of other loci. The other features of epistasis include that, it was fairly common for the same locus to get involved in interactions with more than one other locus; and epistatic interactions were sensitive to environmental affections. QE effects were detected more often than QTL main effects, might indicate that gene expression for quantitative trait could be greatly affected by environments.